Clustering pattern and evolution characteristic of microRNAs in grass carp (Ctenopharyngodon idella) - Huiqin Niu; Yifan Pang; Lingli Xie; Qiaozhen Yu; Yubang Shen; Jiale Li; Xiaoyan Xu (BMC Genomics, 2023)
Abstract Background A considerable fraction of microRNAs (miRNAs) are highly conserved, and certain miRNAs correspond to genomic clusters. The clustering of miRNAs can be advantageous, possibly by allowing coordinated expression. However, little is known about the evolutionary forces responsible for the loss and acquisition of miRNA and miRNA clusters. Results The results demonstrated that several novel miRNAs arose throughout grass carp evolution. Duplication and de novo production were critical strategies for miRNA cluster formation. Duplicates accounted for a smaller fraction of the expansion in the grass carp miRNA than de novo creation. Clustered miRNAs are more conserved and change slower, whereas unique miRNAs usually have high evolution rates and low expression levels. The expression level of miRNA expression in clusters is strongly correlated. Conclusions This study examines the genomic distribution, evolutionary background, and expression regulation of grass carp miRNAs. Our findings provide novel insights into the genesis and development of miRNA clusters in teleost.